Association of self‐reported religiosity with the development of major depression in multireligious country Japan. Issue 10 (5th July 2020) - Kobayashi, Daiki; First, Michael B.; Shimbo, Takuro; Kanba, Shigenobu; Hirano, Yoji
Abstract : Aim: In Western Christian countries, religiosity is generally believed to be associated with a lower risk for depression, which is supported by epidemiological evidence. However, the association between religiosity and depression in multireligious countries is unknown. The objective was to evaluate the association between religiosity and subsequent depression in a multireligious population. Methods: A longitudinal study was conducted in a large hospital in Tokyo, Japan, from 2005 to 2018. All participants who underwent health check‐ups without a prior history of depression or depression at baseline were included. Our outcome was development of major depressive disorder (MDD), which was compared according to the degree of religiosity, adjusting for potential confounders. Results: Among 67 723 adult participants, those who were more religious tended to be older, female, married, and to have healthier habits but also more medical comorbidities at baseline. During a median follow‐up of 2528 days, 1911 (2.8%) participants developed MDD. Compared to the reference group, religious group participants tended to have higher odds ratios (OR) for developing MDD in a dose‐dependent manner. Among them, the extremely religious group (OR, 1.51; 95% confidence interval [CI], 1.28–1.78) and the moderately religious group (OR, 1.30; 95% CI, 1.14–1.49) were statistically associated with increased development of MDD compared to the not‐religious‐at‐all group. Those who had increased their religiosity from baseline had statistically lower development of MDD (OR, 0.85; 95% CI, 0.75–0.97) compared to those who remained in the same degree of religiosity from baseline. Conclusion: Religiosity was associated with future MDD in a dose‐dependent manner in a multireligious population, which was in the opposite direction from that seen in previous Western longitudinal studies.